Effectiveness of High-Intensity Interval Training and Continuous Moderate-Intensity Training on Blood Pressure in Physically Inactive Pre-Hypertensive Young Adults - Anil T John; Moniruddin Chowdhury; Md. Rabiul Islam; Imtiyaz Ali Mir; Md Zobaer Hasan; Chao Yi Chong; Syeda Humayra; Yukihito Higashi (Journal of Cardiovascular Development and Disease, 2022)
The likelihood of pre-hypertensive young adults developing hypertension has been steadily increasing in recent years. Despite the fact that aerobic exercise training (AET) has demonstrated positive results in lowering high blood pressure, the efficacy of different types of AET among pre-hypertensive young adults has not been well-established. The objective of this study was to evaluate the effectiveness of high-intensity interval training (HIIT) and continuous moderate-intensity training (CMT) on the blood pressure (BP) of physically inactive pre-hypertensive young adults. In total, 32 adults (age 20.0 ± 1.1 years and BMI 21.5 ± 1.8) were randomly assigned to three groups: HIIT, CMT and control (CON). The HIIT and CMT groups participated in 5 weeks of AET, while the CON group followed a DASH diet plan only. The HIIT protocol consisted of a 1:4 min work to rest ratio of participants, at an 80–85% heart rate reserve (HR-reserve) and a 40–60% HR-reserve, respectively, for 20 min; the CMT group exercised at 40–60% of their HR-reserve continuously for 20 min. In both the HIIT and CMT groups, systolic blood pressure (SBP) (3.8 ± 2.8 mmHg, p = 0.002 vs. 1.6 ± 1.5 mmHg, p = 0.011) was significantly reduced, while significant reductions in the diastolic blood pressure (DBP) (2.9 ± 2.2 mmHg, p = 0.002) and mean arterial pressure (MAP) (3.1 ± 1.6 mmHg, p < 0.0005) were noted only in the HIIT group. No significant differences in SBP (−0.4 ± 3.7 mmHg, p = 0.718), DBP (0.4 ± 3.4 mmHg, p = 0.714), or MAP (0.1 ± 2.5 mmHg, p = 0.892) were observed in the CON group. Both HIIT and CMT decreased BP in physically inactive pre-hypertensive young adults; however, HIIT yielded more beneficial results in terms of reducing the SPB, DBP and MAP.